2023
DOI: 10.1021/acsenergylett.3c01139
|View full text |Cite
|
Sign up to set email alerts
|

Boronization of Nickel Foam for Sustainable Electrochemical Reduction of Nitrate to Ammonia

Zhong-Hua Xue,
Han-Cheng Shen,
Peirong Chen
et al.

Abstract: Electrochemical reduction of aqueous nitrates has emerged as a sustainable and practical approach in combining water treatment and ammonia fertilizer synthesis. However, the development of highly integrated catalytic electrodes with consistently high activity from non-noble metals remains a challenging issue despite the potential to greatly decrease costs and promote real-world applications. Here, we report a high-performance electrode with electron-abundant surfaces obtained from direct boronization of nickel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Carbon material carriers (e.g., activated carbon, carbon cloth, carbon paper, carbon nanofibers, and graphene) also have a large specific surface area, dense pore structure, and good electrical conductivity, which allow smaller sized metal particles to be adequately distributed on the surface of the carriers while enabling rapid electron transfer from the carrier shell thereby activating the catalytic effect of the metal. Nickel foam , and copper foam have excellent porous structures and large specific surface areas while carrying the metal elements themselves; thus, they can be used as self-supporting materials.…”
Section: Rational Selection and Design Of Electrocatalyst Materialsmentioning
confidence: 99%
“…Carbon material carriers (e.g., activated carbon, carbon cloth, carbon paper, carbon nanofibers, and graphene) also have a large specific surface area, dense pore structure, and good electrical conductivity, which allow smaller sized metal particles to be adequately distributed on the surface of the carriers while enabling rapid electron transfer from the carrier shell thereby activating the catalytic effect of the metal. Nickel foam , and copper foam have excellent porous structures and large specific surface areas while carrying the metal elements themselves; thus, they can be used as self-supporting materials.…”
Section: Rational Selection and Design Of Electrocatalyst Materialsmentioning
confidence: 99%
“…In particular, the pollution of nitrate in groundwater can directly or indirectly harm human health. 12,13 In recent years, there have been various methods for treating nitrate pollution in soil and water, such as bacterial denitrification, 14,15 ion reverse osmosis, 16,17 and electrodialysis. 18 However, these methods cannot effectively eliminate nitrate, let alone converting it into valuable chemical products.…”
Section: Introductionmentioning
confidence: 99%
“…Transition metals with strong redox properties due to the unsaturated d-electron shells have been widely used for the NITRR. [15][16][17][18][19][20] Since zirconia (ZrO 2 ) is highly chemically stable in acidic or alkaline environments, it can be potentially used as a catalyst, 21 catalyst additive 22 and carrier. 23 For the NITRR, Xia et al reported that Cu-loaded ZrO 2 nanofibers significantly inhibited the competitive hydrogen evolution reaction during nitrate reduction.…”
mentioning
confidence: 99%